ANALISIS POSISI BERSAING PERUSAHAAN BATIK MENGGUNAKAN THE INDUSTRY ATTRACTIVENES BUSINESS STRENGTH MATRIX (MDTI)STUDY KASUS DI TOBAL BATIK - Dwirainaningsih, Yustiana; Kuswardani, Indah (BAPPEDA Kota Pekalongan, 2019)
Tobal Batik is a home industry that is engaged in the production and sale of batik cloth and batik clothing that is located at Jalan Terai No. 24 Pekalongan The number of other home industries which are engaged in selling batik has quite prospective business opportunities. The increasingly tight competition among batik sellers requires Tobal Batik management to be able to anticipate the emergence of threats from competitors and be able to take advantage of the opportunities and strengths the company has. To achieve this goal, Tobal Batik needs to pay attention to two main factors in the company, namely external and internal factors. External factors are factors that are not influenced by company policy, while internal factors can be influenced by company policy to optimize sales volume that is entirely within the control of the company. To analyze these external and internal factors, a purposive samplin can be used whose purpose is to determine the position of Tobal Batik in the market based on the strengths, weaknesses, opportunities and threats that the company has. Whereas in analyzing business opportunities and the extent to which products produced by Tobal Batik are able to compete in the market, it will be analyzed using the MDTI matrix which serves to see the marketing position of Tobal Batik based on market growth and market share. In order to create a competitive space, companies need to make plans in marketing strategies, so that product sales can increase in the market and provide benefits for the company. Keywords: Marketing strategy, Competitive position, MDTI